Efficacy of the Star Excursion Balance Tests in Detecting Reach Deficits in Subjects With Chronic Ankle Instability - Olmsted, Lauren C. (attr, 2002)
Objective: Chronic instability after lateral ankle sprain has been shown to cause balance deficits during quiet standing. Although static balance assessment in those with ankle instability has been thoroughly examined in the literature, few researchers have studied performance on more dynamic tasks. Our purpose was to determine if the Star Excursion Balance Tests (SEBTs), lower extremity reach tests, can detect deficits in subjects with chronic ankle instability. Design and Setting: We performed all testing in a university athletic training facility. We tested lower extremity reach using the SEBTs, which incorporates single-leg stance with maximal reach of the contralateral leg. Subjects: Twenty subjects with unilateral, chronic ankle instability (age = 19.8 ± 1.4 years, height = 176.8 ± 4.5 cm, mass = 82.9 ± 21.2 kg) and 20 uninjured subjects matched by sex, sport, and position (age = 20.2 ± 1.4 years, height = 178.7 ± 4.1 cm, mass = 82.7 ± 19.9 kg). Measurements: We measured the reach distances in centimeters (cm) and averaged 3 reaches in each of the 8 directions while the subjects stood on each leg for data analysis. Results: The group with chronic ankle instability demonstrated significantly decreased reach while standing on the injured limb compared with the matched limb of the uninjured group (78.6 cm versus 82.8 cm). Additionally, subjects with chronic ankle instability reached significantly less when standing on their injured limbs as compared with their uninjured limbs (78.6 cm versus 81.2 cm). Conclusions: The SEBTs appear to be an effective means for determining reach deficits both between and within subjects with unilateral chronic ankle instability.